Mobile Minos elements from Drosophila hydei encode a two-exon transposase with similarity to the paired DNA-binding domain. - Franz, G (1994)
Elements related to the Tc1-like Minos mobile element have been cloned from Drosophila hydei and sequenced. Southern blot and sequence analyses show that (i) the elements are actively transposing in the Drosophila hydei germ line, (ii) they are characterized by a striking degree of sequence and size homogeneity, and (iii) like Tc1, they insert at a TA dinucleotide that is probably duplicated during the process. The nucleotide sequences of two elements, Minos-2 and Minos-3, differ at only one position from each other and contain two nonoverlapping open reading frames that are separated by a putative 60-nucleotide intron. The amino-terminal part of the Minos putative transposase shows sequence similarity to the paired DNA-binding domain. Forced transcription of a modified Minos element that was introduced into the Drosophila melanogaster germ line by P element-mediated transformation resulted in the production of accurately spliced polyadenylylated RNA molecules. It is proposed that Minos-2 and/or Minos-3 may encode an active transposase containing an amino-terminal DNA-binding domain that is distantly related to the paired DNA-binding domain.